Development of matrix solid-phase dispersion coupled with high-performance liquid chromatography for determination of jolkinolide A and jolkinolide B in Euphorbia fischeriana Steud. Issue 15 (3rd August 2017) - Cai, Defu; Zhai, Weiyu; Zhang, Qi; Liu, Jianhua; Sun, Yu; Liu, Lei; Liu, Jicheng
Abstract: A novel and simple method was established for the extraction and determination of jolkinolide A and B in Euphorbia fischeriana Steud. using matrix solid-phase dispersion (MSPD) extraction and high-performance liquid chromatography (HPLC). The optimised conditions for the MSPD extraction were determined to be that silica gel was served as dispersant, the mass ratio of sample to silica gel was selected to be 1:4, and 5 mL of acetonitrile was used as elution solvent. The method exhibited a good performance in terms of linearity ( r 2 ≥ 0.9997) and the limits of detection in the range of 0.052–0.065 μg mL −1 . The recoveries were in the range of 90.2–98.9% with relative standard deviations (RSDs) ranging from 1.3 to 3.5%. The extraction efficiencies obtained by the MSPD were higher than other extraction method with less cost of sample and solvent. At last, the optimised method was applied for analysing real samples. Abstract :